Rapid neurogenic differentiation of human mesenchymal stem cells through electrochemical stimulation - Jaiswal J.; Dhayal M. (My University, 2025)
The neurogenic differentiation of human mesenchymal stem cells (hMSCs) has been substantially handicapped with the choice of chemical or electrical stimulations for long durations. We demonstrate an innovative strategy of stimulation with <1.0 V for <200 s to achieve hMSCs differentiation towards neural progenitor cells within 24 h and their commitment towards differentiation to neurons on day 3 with the use of three-electrode electrostimulation. Stimulated hMSCs (ES hMSCs) showed elevated expression of neural-specific markers and mitochondrial membrane potential. A voltage bias of ±0.5 V and ±1.0 V did not show any adverse effect on cell viability and proliferation, whereas cells stimulated with ±1.5 V showed an upsurge in the dead cell populations. With the progression of time after stimulation, a rise in mitochondrial membrane potential (MMP, ΔΨ M) was observed in the ES hMSCs and thereby generating intracellular reactive oxygen species (ROS), acting as a key messenger to induce neuronal differentiation. The stratagem may provide insightful handles to circumvent neurodifferentiation impediments, a focal issue for regenerative medicine. © 2023